2019
DOI: 10.1002/aoc.5091
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium (IV) porphyrin graphene oxide: a new and efficient catalyst for the synthesis of 3,4‐dihydropyrimidin‐2(1H)‐ones

Abstract: A covalently cross‐linked graphene oxide (GO) as a catalyst was prepared by a cross‐linking process using the nucleophilic reaction of zirconium (IV)‐coordinated 5,10,15,20‐tetrakis (aminophenyl)porphyrin (ZrPPh) with carboxyl groups of the edges of GO (GO‐ZrPPh). The chemical structure of catalyst was characterized by different analyses such as FT‐IR, SEM, TEM, EDS, ICP, TGA and UV. All analyses confirm the occurrence of successfully covalent immobilization of ZrPPh on the GO. Also, TEM and SEM images show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 61 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…Ghadamyari et al [ 153 ] reported synthesis of dihydropyrimidin‐(1 H )‐ones via one‐pot three‐component condensation reaction of ethyl acetoacetate, various aldehydes, and urea in the presence of zirconium (IV) porphyrin GO (GOZrPPh) as a catalyst without any solvent at 70°C for 180 min (Scheme 23). To optimize the reaction conditions, 0.28 mol% of catalyst was selected for this reaction.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%
“…Ghadamyari et al [ 153 ] reported synthesis of dihydropyrimidin‐(1 H )‐ones via one‐pot three‐component condensation reaction of ethyl acetoacetate, various aldehydes, and urea in the presence of zirconium (IV) porphyrin GO (GOZrPPh) as a catalyst without any solvent at 70°C for 180 min (Scheme 23). To optimize the reaction conditions, 0.28 mol% of catalyst was selected for this reaction.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%
“…In show the merit of the present study, the results of using complex 1 for the synthesis of product 5a by reacting benzaldehyde, ethyl acetoacetate, and urea with other homogeneous and heterogeneous catalysts were compared ( Table 4, entries [3][4][5][6][7][8][9][10][11][12][13][14]. According to the obtained results [7,9,13,24,27,[31][32][33][53][54][55] our catalyst shows better catalytic activity with a shorter reaction time using solvent-free conditions with good recyclability. Apparently, the long fluoroalkyl chain in the sulfonate must be responsible for the hydrophobicity and increasing the catalytic activity.…”
Section: S C H E M Ementioning
confidence: 99%
“…Generally, dihydropyrimidinones are synthesized by the three‐component Biginelli reaction of aldehyde, 1,3‐dicarbonyl compound and urea, and much work on improving these protocols towards reaching milder reaction conditions and higher yields has been actively pursued. Until now, various catalysts and catalytic systems have been developed, including BF 3 ·OEt 2 , ZrCl 4 or ZrOCl 2 , InCl 3 , InBr 3 , YCl 3 , TaBr 5 , VCl 3 , metal triflates (Y, Sr, In, Cu), Fe (OTs) 3 · 6H 2 O, Mn (OAC) 3 · 2H 2 O, Y (NO 3 ) 3 · 6H 2 O, H 3 BO 3 , PPh 3 , Cp 2 Ti‐based Lewis acids, TBAB, Ag 3 PW 12 O 40 , SiO 2 ‐Cl, Fe 3 O 4 /PAA‐SO 3 H, nanomagnetic supported sulfonic acid, FeCl 3 ‐supported nanoporous silica, precious metals (Pt, Pd, Ru) on graphene oxide nanoparticle catalyst, zirconium porphyrin graphene oxide, H 3 PW 12 O 40 supported on ZIF‐9(NH 2 ), Cu@SBA‐15, and others . However, these catalysts of the Biginelli reaction procedures are associated with harsh reaction conditions, expensive and corrosive reagents, the use of volatile organic solvents, poor substrate generality, unsatisfactory yields, longer reaction times and poor catalyst recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, nanoparticles have been widely used as solid supports for the immobilization of homogeneous catalysts. [8][9][10] For example, silica materials, [11] polymers, [12] graphene oxide, [13][14][15][16] carbon nanotubes, [17] iron oxide, [18] ionic liquids, [19,20] boehmite nanoparticles, [21,22] biochar, [23] magnetic nanoparticles, [24][25][26] etc. were employed as support for the stabilization of homogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%